The other crisis: the economics and financing of maternal, newborn and child health in Asia - Anderson, I.; Axelson, H.; Tan, Boon (Oxford University Press, 2010)
The Global Financial Crisis (GFC) of 2008/2009 was the largest economic slowdown since the Great Depression. It undermined the growth and development prospects of developing countries. Several recent studies estimate the impact of economic shocks on the poor and vulnerable, especially women and children. Infant and child mortality rates are still likely to continue to decline, but at lower rates than would have been the case in the absence of the GFC.Asia faces special challenges. Despite having been the fastest growing region in the world for decades, and even before the current crisis, this region accounted for nearly 34% of global deaths of children under 5, more than 40% of maternal deaths and 60% of newborn deaths. Global development goals cannot be achieved without much faster and deeper progress in Asia.Current health financing systems in much of Asia are not well placed to respond to the needs of women and their children, or the recent global financial and economic slowdown. Public expenditure is often already too low, and high levels of out-of-pocket health expenditure are an independent cause of inequity and impoverishment for women and their children. The GFC highlights the need for reforms that will improve health outcomes for the poor, protect the vulnerable from financial distress, improve public expenditure patterns and resource allocation decisions, and so strengthen health systems.This paper aims to highlight the most recent assessments of how economic shocks, including the GFC, affect the poor in developing countries, especially vulnerable women and children in Asia. It concludes that conditional cash transfers, increasing taxation on tobacco and increasing the level, and quality, of public expenditure through well-designed investment programmes are particularly relevant in the context of an economic shock. That is because these initiatives simultaneously improve health outcomes for the poor and vulnerable, protect them from further financial distress, improve public financing and/or provide a much-needed counter-cyclical stimulus at times of economic slowdown.